2017
DOI: 10.1111/cei.12960
|View full text |Cite
|
Sign up to set email alerts
|

Human gestation-associated tissues express functional cytosolic nucleic acid sensing pattern recognition receptors

Abstract: Summary The role of viral infections in adverse pregnancy outcomes has gained interest in recent years. Innate immune pattern recognition receptors (PRRs) and their signalling pathways, that yield a cytokine output in response to pathogenic stimuli, have been postulated to link infection at the maternal–fetal interface and adverse pregnancy outcomes. The objective of this study was to investigate the expression and functional response of nucleic acid ligand responsive Toll‐like receptors (TLR‐3, −7, −8 and −9)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…These results showed that BVDV has the ability to cross the placenta and infect the fetus due to insufficient development of the fetal immune system and that RNA helicases RIG-I and MDA5 can be induced in infected fetuses. RIG-I, as well as MDA5, TLR-3, TLR-7 and TLR-8, were also found to be expressed by the term placenta, choriodecidua and amnion in a second study [31]. Our results may indicate that RIG-I activate in chorionic villi and decidua the same intracellular signalling pathway as IFI16.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These results showed that BVDV has the ability to cross the placenta and infect the fetus due to insufficient development of the fetal immune system and that RNA helicases RIG-I and MDA5 can be induced in infected fetuses. RIG-I, as well as MDA5, TLR-3, TLR-7 and TLR-8, were also found to be expressed by the term placenta, choriodecidua and amnion in a second study [31]. Our results may indicate that RIG-I activate in chorionic villi and decidua the same intracellular signalling pathway as IFI16.…”
Section: Discussionsupporting
confidence: 57%
“…It was described previously that RIG-I acts in parallel with DAI in an RNA polymerase IIIdependent manner to initiate inflammatory and antiviral glial responses to HSV-1 infection [47]. RIG-I, as well as MDA5, TLR-3, TLR-7 and TLR-8, were also found to be expressed by the term placenta, choriodecidua and amnion in a second study [31]. These results showed that BVDV has the ability to cross the placenta and infect the fetus due to insufficient development of the fetal immune system and that RNA helicases RIG-I and MDA5 can be induced in infected fetuses.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…A still-controversial uterine microbiota could help to model the interaction between the feto-placental unit and the maternal immune system [1,12]. [13,14]), competent to recognize microbial constituents translocated within the blood and more in general to integrate sterile and microbial stimuli. It might be relevant that decidual cells express innate pattern recognition receptors (e.g.…”
Section: Maternal Microbiotamentioning
confidence: 99%
“…It might be relevant that decidual cells express innate pattern recognition receptors (e.g. [13,14]), competent to recognize microbial constituents translocated within the blood and more in general to integrate sterile and microbial stimuli. Because of the signals generated by the feto-placental unit and by the decidua (bioactive microvesicles, hormones, cytokines, etc.…”
Section: Maternal Microbiotamentioning
confidence: 99%